A retrospective naturalistic study on the psychopharmacological treatment of schizoaffective disorder. (September 2021) - Muñoz-Negro, José E.; Aguado Bailón, Lidia; Calvo Rivera, Pilar; Cervilla, Jorge A.
Abstract : Evidence on the effectiveness of psychopharmacological treatment of schizoaffective disorder is scarce and mostly comes from indirect, nonspecific sources. We carried out a large retrospective study ( n = 770) of every other consecutively numbered clinical record with a recorded ICD-10 diagnosis of schizoaffective disorder in the Andalusian Health Service record system. We gathered sociodemographic, drug treatment and clinical outcomes such as improvement, relapses and change over time on DSM-5 psychotic dimensions. We analyzed data to explore associations between drug use and clinical improvement. Antipsychotics were the most commonly used drugs (77%). 22.4% of patients experienced at least a mild improvement. Clozapine (odds ratio [OR] = 2.4) and aripiprazole (OR = 2.3) for global improvement, and quetiapine (OR = 3.5) for depression were the most effective drugs. Antidepressants, mood stabilizers and benzodiazepines were also associated with a better outcome in some DSM-5 dimensions such as delusions, hallucinations and language, respectively. Antipsychotic monotherapy was not associated with a better outcome. Our findings corroborate the role of antipsychotics as the essential psychopharmacological treatment for different symptoms of schizoaffective disorder. However, the role of mood stabilizers, antidepressants or BZD is controversial and should be individually considered.